Top Incomes, Rising Inequality, and Welfare - Kevin J. Lansing; Agnieszka Markiewicz (Norges Bank, 2012)
This paper develops a general-equilibrium model of skill-biased technological change that approximates the observed shifts in the shares of wage and non-wage income going to the top decile of U.S. households since 1980. Under realistic assumptions, we find that all agents can benefit from the technology change, provided that the observed rise in redistributive transfers over this period is taken into account. We show that the increase in capital's share of total income and the presence of capital-entrepreneurial skill complementarity are two key features that help support the wages of ordinary workers as the new technology diffuses.
hdl:11250/2496828
Keywords: E32; E44; H23; O33; 330; income inequality; skill-biased technological change; capital-skill complementarity; redistribution; welfare